Questions Students Have Method: Improvement Creativity and Learning Outcomes in Islamic Education - Hafshah Safrindra F; Asrori; Rusman (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2023)
The research objective was to find out the application of the Questions Students Have method to increase creativity and learning outcomes at SMPN 1 Muhammadiyah Surabaya. This research is a classroom action research. Observation and test data collection techniques. Analytical descriptive data analysis technique. Research shows that 1) The percentage of student creativity increases dramatically in each cycle, with student creativity included in the sufficient category in the first cycle 28.5% good category, 38.1% sufficient category and 33.3% lacking and developing in the second cycle good category 52.3%, sufficient category 30.8 and less category 9.5%. 2) Student learning outcomes in each cycle increased by 100%, the completeness level in the first cycle was 28.6%, the average learning result was 70.71%, the mastery level in the second cycle was 100%, with an average learning result of 93.57%.